Evaluasi Konsentrasi Karboksimetilselulosa-Alginat Formula Pasta Gigi Antiseptik Ekstrak Etanol Daun Seledri (Apium graveolens L.) - Suprianto Suprianto; Samran Samran; Muhammad Gunawan; Melati Yulia Kusumastuti (LPPM STIKes Indah Medan, 2022)
Maceration of Celery leaves using 96% ethanol solvent was used to make the extract. Toothpaste is formulated with carboxymethylcellulose and alginate binders. The active ingredient in the form of ethanol extract of Celery leaves has the potential for antibacterial. This study was to evaluate the concentration of carboxymethylcellulose-alginate in the preparation of antiseptic toothpaste of ethanol extract of Celery leaves. Evaluation of production results consisted of organoleptic, homogeneity, spreadability, foam formation, acidity and viscosity. The higher the concentration of carboxymethylcellulose, the lower the foam and spreadability and the higher the viscosity, while the alginate concentration is the opposite. Carboxymethylcellulose-alginate affects the evaluation parameters of antiseptic toothpaste preparations ethanol extract of Celery leaves